Optimizing The Potential of Productive Waqf in Encouraging Sharia Economic Growth - Siti Habibatur Rahma; Wildatun Musyarrofah (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
The purpose of this study is to identify wakaf potential and analyze strategies for optimal pengelolaannya to make a more significant contribution to the development of the syariah economy. The research method used is qualitative with a descriptive approach, demonstrating the researcher's efforts to solve actual problems through data collection, compilation, classification, analysis, and interpretation. The data collection technique used is library research, in which the researcher reads, studies, and analyzes books, journals, and articles written by researchers. The results indicate that professional and productive management, a transparent and accountable management system, and the use of digital technology can optimize the potential of waqf. In addition, good synergy starts from the government, Islamic financial institutions, and the community is a crucial factor in strengthening the waqf ecosystem. With the right strategy, wakaf has the potential to become one of the main pillars in the development of the various sectors of the syariah economy, particularly in the areas of education, health, and micro, small, and medium business (UMKM).